2010
DOI: 10.1021/bc100137x
|View full text |Cite
|
Sign up to set email alerts
|

Improved 18F Labeling of Peptides with a Fluoride-Aluminum-Chelate Complex

Abstract: We reported previously the feasibility to radiolabel peptides with fluorine-18 (18F) using a rapid, one-pot, method that first mixes 18F− with Al3+, and then binds the (Al18F)2+ complex to a NOTA ligand on the peptide. In this report, we examined several new NOTA ligands and determined how temperature, reaction time, and reagent concentration affected the radiolabeling yield. Four structural variations of the NOTA ligand had isolated radiolabeling yields ranging from 5.8% to 87% under similar reaction conditio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
182
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 184 publications
(189 citation statements)
references
References 34 publications
6
182
1
Order By: Relevance
“…This process requires a long synthesis time of approximately 2 h. We were able to radiolabel Affibody molecules with 18 F within 30 min using a 2-step, 1-pot reaction. In addition, in future studies the specific activity of 18 F-NOTA-Z HER2:2395 may be improved by using different chelators and solvents (29,30).…”
Section: Discussionmentioning
confidence: 99%
“…This process requires a long synthesis time of approximately 2 h. We were able to radiolabel Affibody molecules with 18 F within 30 min using a 2-step, 1-pot reaction. In addition, in future studies the specific activity of 18 F-NOTA-Z HER2:2395 may be improved by using different chelators and solvents (29,30).…”
Section: Discussionmentioning
confidence: 99%
“…We also had to purify our 18 F-labeled peptide with HPLC to obtain a high-specific-activity preparation. Recently, McBride et al have shown that the AlF method can be further optimized using other chelators (19,29). They developed a 1-pot method that provides a high labeling efficiency and specific activity with no more than only solid-phase extraction purification needed before formulation for injection.…”
Section: Discussionmentioning
confidence: 99%
“…18 F. A variety of methods to label proteins with 18 F have been described previously (Guhlke et al, 1994;Cai et al, 2008;McBride et al, 2010); however, labeling with this particular isotope generally remains a challenge because of its short half-life, low radiochemical yields, and low specific activities. A commonly used approach uses the 18 F-labeled amine-reactive intermediate N-succinimidyl 4-[…”
Section: Chemistry and Biologymentioning
confidence: 99%
“…This approach involves the 18 F-labeling of the intermediate followed by conjugation to the protein. An approach using a bifunctional chelate has also been described previously (McBride et al, 2009(McBride et al, , 2010.…”
Section: Chemistry and Biologymentioning
confidence: 99%